'It breaks my heart': Healthcare practitioners' caring for families with epidermolysis bullosa - Antoinette V. Chateau; Colleen Aldous; Ncoza Dlova; David Blackbeard (AOSIS, 2023)
Background: Epidermolysis bullosa (EB) is a painful genodermatosis presenting with skin fragility and blisters. There is no cure; the prognosis is guarded and depends on the subtype of the disease. Managing these patients can be emotionally challenging for healthcare practitioners. Aim: To determine the perceptions, impact, and needs of healthcare practitioners (HCP) caring for patients and their families with EB. Setting: Nelson Mandela School of Medicine, Durban and Grey's Hospital, Pietermaritzburg, KwaZulu-Natal. Methods: The study was guided by interpretative phenomenological analysis. Individual in-depth interviews were conducted with 10 healthcare practitioners. Guba's trustworthiness framework was used to ensure rigour. Results: Six global themes were identified, each related primarily to the perceptions, impact, and needs of healthcare practitioners. The experiences and perceptions of healthcare practitioners were that caring for patients with an incurable disease such as EB could negatively impact healthcare practitioners. There were divergent views among the disciplines of HCPs regarding the extent of care in a resource-limited environment. This resulted in negative emotions, ethical concerns, and a need for continued medical education and the application of coping strategies. Healthcare practitioners observed that patients and their families were vulnerable, requiring comprehensive biopsychosocial care. Conclusion: Healthcare practitioners should be aware of their emotional challenges, seek support where necessary, and use effective coping strategies and self-care. Contribution: The concerns and needs of healthcare practitioners are highlighted and interventional strategies to assist healthcare practitioners are suggested which will ultimately improve patient care.